A dazzling disk - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
What finally won women over to line up to visit the famous community telecentre in Nakaseke in Uganda? A CD-ROM disk with market and price information about the products they sell. One woman is paid to train the others in computer skills. Now plans...